Impacts of Payment for Forest Environmental Services in Cat Tien National Park - Pham Thu Thuy; Nguyen, T.D.; Dao, C.T.L.; Hoang, L.T.; Pham, L.H.; Nguyen, L.T.; Tran, B.K. (MDPI, 2021)
This paper assesses the impacts of Payment for Forest Environmental Services (PFES) in Cat Tien National Park, Vietnam. We analyze the impacts and additionality of PFES on local livelihoods by comparing the socio-economic situations in four pairs of villages before and after its implementation, and between places where PFES is and is not applied. In total, 149 people participated in focus group discussions, while 244 households (123 in areas with PFES and 121 in areas without) took part in household surveys. Our research shows that 92% of the people interviewed are from ethnic minorities participating and benefiting directly from PFES. In villages with PFES, the numbers of participating households ranged from 45% to 88% of all poor households in those villages. Of the poor households participating in PFES in the studied villages, 22% have no source of cash income other than their forest protection contracts, while 81.4% have escaped poverty, based on self-defined poverty criteria, through additional income from forest protection. Since the implementation of PFES, the area of forests allocated for community and household management is estimated to be three to 3.64 times higher than it had been previously. Although the number of communities under PFES contracts has not changed, the number of households participating in forest protection contracts is now much lower than before PFES started. On average, PFES contributes 16% to 74% of total household income in villages with PFES. Incomes in places with PFES are significantly higher than in places without. Although our research demonstrates immediate positive socio-economic impacts on livelihoods, it also highlights weaknesses in the current monitoring and evaluation system and a lack of reliable data for measuring PFES impacts in Cat Tien National Park.